Opioid agonist therapy trajectories among street entrenched youth in the context of a public health crisis. (August 2020) - Giang, Valerie; Thulien, Madison; McNeil, Ryan; Sedgemore, Kali; Anderson, Haleigh; Fast, Danya
Abstract: North America is in the midst of an overdose crisis that is having devastating effects among street entrenched youth (<30 years of age). Opioid agonist therapy (OAT) is a cornerstone of the public health response to this crisis; yet, we struggle to connect youth to OAT across numerous settings. This qualitative study examined perspectives on OAT among street entrenched youth and their providers in Vancouver, Canada. Our findings reveal youth's hopes and fears surrounding making a "full" recovery from past substance use. Youth often equated getting off opioids with "getting back to normal" and the ability to pursue "normal" kinds of futures. While many initiated OAT for short periods of time (<one month) to mediate the discomfort of withdrawal during in-patient treatment, adherence to medications like methadone and buprenorphine over the longer term did not fit with many youth's visions of "normal" futures. A number of polysubstance using youth did not access OAT, despite its lifesaving potential. Youth who did access OAT often preferred methadone because of its perceived ability to mediate longstanding physical and mental health issues. Participants who accessed OAT had the most success with adherence when they were invested in this treatment modality and actively involved in decision making around what kind of medication would work best for them, and for how long. In the absence of this collaboration, many youth made the decision to taper off of OAT independently, frequently resulting in relapse and heightened overdose risk. Highlights: The overdose crisis in North America is having devastating effects on youth. Opioid agonist therapy (OAT) is a cornerstone of the response to the crisis. Many youth do not view OAT as a part of "full" recovery from opioid use. Many youth pursue OAT to mediate physical and mental health issues. Youth desire ongoing collaboration regarding the length and type of OAT.